Effect of Some Parameters on the Compressive Strength of MWCNT-Cement Composites - Hyukjin Choi; Donghoon Kang; Gang Seok Seo; Wonseok Chung (Advances in Materials Science and Engineering)
Enhancements in the compressive strength of ordinary Portland cement (OPC) mortar upon the incorporation of multiwalled carbon nanotubes (MWCNTs) were investigated. The MWCNT concentration, water/cement (W/C) ratio, curing age, and MWCNT concentration control method were selected as experimental parameters, and their effect on the compressive strength of the MWCNT-cement composites was examined. Here, the MWCNT concentration was varied from 0.25 wt% to 1.0 wt%, while W/C ratios in the range of 0.35 to 0.70 were employed. Curing ages of 7, 14, and 28 days were also utilized. To compare methods for controlling the MWCNT concentration, solutions were prepared by either adjusting the MWCNT content during mixing or controlling the MWCNT concentration by adding distilled water to solutions with a high MWCNT content. The compressive strength of the MWCNT-cement composites when considering the aforementioned parameters was compared to that of OPC mortar. Scanning electron microscopy (SEM) was also used to investigate the microstructure of the MWCNT-cement samples.